Pop masculinities the politics of gender in twenty-first century popular music - Hansen, Kai Arne ca. 20./21. Jh (Oxford University Press, 2022)
Introduction. Like Pinocchio -- Separating the Men from the Boys : New Masculinities, Pop Music, and the Social Politics of Interpretation -- Good Boy Gone Bad : Fashioning a Post Boy Band Masculinity -- A Different Country? Lil Nas X, the Sound of the Internet, and Queering the Cowboy -- Beyond Bieber Fever -- Dangerous and (In)Vulnerable : Aestheticizing Violence and Dancing in Sin City -- From Boy Band to Man Band : Take That, Age(ing), and the Display of Self-Irony -- Conclusion. Fade-Out
Includes bibliographical references and index
Keywords: Popular music / History and criticism; Masculinity in music